The analysis of mixture kinematics in the mixer body frame with a screw elevator with variable generatrix - Коробко, Богдан Олегович; Васильєв, Олексій Сергійович; Рогозін, Іван Анатолійович (Eastern-European Journal of Enterprise Technologies, 2015)
To improve the mixing intensity and vertical screw belt mortar mixer efficiency, it was proposed to use screw belts with generatrices that have a variable inclination angle to the screw axis, depending on the placement height. Studies of working processes for machines with a new mixer design have not been performed or are unknown. Therefore, a theoretical research and analysis of the mixture kinematics in the mixer body with new geometric parameters were conducted. The motion of elementary discrete mixture particle was considered as complex. It was divided into translational, together with a movable coordinate system, connected with the working body, and relative, by the screw belt surface. For given conditions, the motion patterns of the mixture particle were built. It has allowed to obtain the equations of motion coordinates of the particles, the equations for determining their relative and translational velocities, as well as for determining the direction of the velocity vectors. All types of accelerations that occur under these conditions were found. The equations for determining the magnitude and direction of the acceleration vectors of the relative and translational motions, as well as the Coriolis acceleration were obtained. The dependencies and motion patterns can be used for further research of new mixers with variable inclination angle of screw belt generatrices, as well as for calculating the forces of resistance to the working body motion and the mixer power consumption. The results may be useful in selecting a rational layout of the working bodies of mortar mixers in the space. This will allow to improve the quality of the design works.